Pusa hispida subsp. botnica Gmelin 1788 - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Pusa hispida subsp. botnica Gmelin 1788 Synonyms: Pusa hispida subsp. annellata (Nilsson 1820); Pusa hispida subsp. octonata (Kutorga 1839); Pusa hispida subsp. undulata (Kutorga 1839). Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Carnivora, pp. 532-628 in Mammal Species of the World: a Taxonomic and Geographic Reference (3 rd Edition), Volume 1, Baltimore :The Johns Hopkins University Press on page 600, DOI: 10.5281/zenodo.7316519